2011
DOI: 10.1556/aagr.59.2011.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of seven pea (Pisum sativum) genotypes with five sowing dates in sandy soil

Abstract: A field experiment was conducted at the Agriculture Faculty Farm of Sebha University during the 2007/2008 and 2008/2009 winter seasons to study the agronomic performance of seven pea genotypes with different sowing dates in sandy soil. The experiment was laid out in a randomized complete block design (RCBD) using a split-plot arrangement with three replicates. The five sowing dates (30 October, 15 November, 30 November, 15 December and 30 December) were assigned to the main plots, while the seven pea genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Higher yield due to the exposure of plants in favorable environmental condition during reproductive stages because it gave highest number of pods and seeds plant -1 . These results are similar with the findings of Hanaa and Ali (2000) [13] where they reported that seed yield of field pea varied among the interaction of variety and sowing date due to variation in number of pods and seeds plant -1 .…”
Section: Seed Yield (Kg Ha -1 )supporting
confidence: 92%
“…Higher yield due to the exposure of plants in favorable environmental condition during reproductive stages because it gave highest number of pods and seeds plant -1 . These results are similar with the findings of Hanaa and Ali (2000) [13] where they reported that seed yield of field pea varied among the interaction of variety and sowing date due to variation in number of pods and seeds plant -1 .…”
Section: Seed Yield (Kg Ha -1 )supporting
confidence: 92%
“…Azmirly cultivar surpassed the Cream 7 in this respect by 40.62 and 30.09 % in the first and second season, respectively. This may be due to the genotypic, environmental interaction (Hanaa and Ali, 2011) .All the interactions involved in this respect were not significant in both seasons.…”
Section: Number Of Branches Per Plantmentioning
confidence: 84%
“…The plants were planted in November and harvested in April at University of Malakand, Khyber Pakhtunkhwa, Pakistan located at coordinates N 34° 40" 318' and E72° 03" 753' at altitude 726 m. The 24 lines were grown in a layout of complete randomized block design with three replicates in row plots as suggested by Hanaa and Ali (2011). The length of each plot was 18 m with a width of 3 m. Each line was planted in a row plot with 75 cm row to row in distance and 10 cm plant to plant in distance (Nisar et al 2011).…”
Section: Plant Materialsmentioning
confidence: 99%